2007
DOI: 10.1172/jci29470
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-enhanced cross-presentation of self antigen breaks T cell tolerance

Abstract: We have developed a model of autoimmunity to investigate autoantibody-mediated cross-presentation of self antigen. RIP-mOVA mice, expressing OVA in pancreatic β cells, develop severe autoimmune diabetes when given OT-I cells (OVA-specific CD8 + T cells) and anti-OVA IgG but not when given T cells alone. Anti-OVA IgG is not directly injurious to the islets but rather enhances cross-presentation of apoptotic islet antigen to the OT-I cells, leading to their differentiation into potent effector cells. Antibody-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 53 publications
2
96
0
Order By: Relevance
“…This is a parameter which is hard to control with either gene gun or electroporation and is not enhanced with the use of cytokines such as GM-CSF or adjuvants such as imiquimod (result not shown). Reports in the literature have previously demonstrated that vaccine induced T-cell responses can be enhanced by Ab [38][39][40]. A recent elegant study by Saenger et al demonstrates that anti-tumor immunity is dramatically enhanced by combination of DNA vaccination and treatment with an anti-TRP-1 Ab [40].…”
Section: Discussionmentioning
confidence: 99%
“…This is a parameter which is hard to control with either gene gun or electroporation and is not enhanced with the use of cytokines such as GM-CSF or adjuvants such as imiquimod (result not shown). Reports in the literature have previously demonstrated that vaccine induced T-cell responses can be enhanced by Ab [38][39][40]. A recent elegant study by Saenger et al demonstrates that anti-tumor immunity is dramatically enhanced by combination of DNA vaccination and treatment with an anti-TRP-1 Ab [40].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by a recent study demonstrating a pathogenic role of autoantibodies by enhancing islet cell antigen presentation to autoreactive T cells (11). Harbers et al (11) showed that both antigen-specific CD8 ϩ T cells and antigenspecific antibodies were necessary for the development of autoimmune diabetes in transgenic mice that express a membranebound form of ovalbumin in pancreatic ␤ cells.…”
mentioning
confidence: 88%
“…Although GAD65Ab are often considered to be an epiphenomenon resulting from the autoimmune destruction of the pancreatic ␤ cells, some studies suggest that they may be involved in antigen processing and presentation and thus modulate the immune response (8)(9)(10). This hypothesis is supported by a recent study demonstrating a pathogenic role of autoantibodies by enhancing islet cell antigen presentation to autoreactive T cells (11). Harbers et al (11) showed that both antigen-specific CD8 ϩ T cells and antigenspecific antibodies were necessary for the development of autoimmune diabetes in transgenic mice that express a membranebound form of ovalbumin in pancreatic ␤ cells.…”
mentioning
confidence: 94%
“…Viruses cDC requirement for LCMV, 35 HSV-1, 36 VSV, 37 influenza, 38 CTL response cDC independence of anti-VSV B and CD4 T-cell response 36,39 Bacteria cDC requirement for anti-Listeria CTL response 11,40 cDC requirement for efficient Mycobacterium tuberculosis CD4 T-cell response 41 cDC requirement for anti-Salmonella response 42,43 cDC independence of UPEC clearance 44 Parasites cDC requirement for anti-Plasmodium 11 and anti-Leishmania response 45,46 Prions cDC requirement for intestinal Scrapie agent neuroinvasion 47 Miscellaneous Tolerance cDC role in Ig complex-mediated priming and tolerization 48,49 cDC independence of peripheral CD4 T-cell tolerization 50 NK responses cDC requirement for NK cell activation by IL-15 trans-presentation 25 NKT responses cDC requirement for glycolipid presentation 51,52 CTL responses cDC requirement for efficient CTL memory generation 27 Respiratory tract cDC requirement for asthma and experimental allergic rhinitis 18,53 Tumor studies cDC requirement for antitumor immunity 52 DC functions by conditional cell ablation A Sapoznikov and S Jung subpopulations and generally provided by non-hematopoietic cells, including stromal and follicular dendritic cells; 58 and (2) the chemokine macrophage migration inhibitory factor (MIF) that controls mature B-and tumor cell survival through triggering of the CD74-CD44 receptor complex. [59][60][61] 70 on pDC.…”
Section: Pathogen Defensementioning
confidence: 99%